Konsep Etnomatematika pada Alat Musik Tradisional Mandailing Natal : Gordang Sambilan - Mutiah Dina Maya; Muhammad Rif’an; Shaqila Rizky D.A; Riani Tazkia Hadi; Elvi Mailani; Mardhiyah Kharismayanda (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This study aims to explore the ethnomathematics concepts embedded in the traditional musical instrument Gordang Sambilan from Mandailing culture and how these concepts can be integrated into mathematics education. Gordang Sambilan, which consists of nine drums of varying sizes, serves not only as a cultural symbol but also as a rich source of mathematical elements, including arithmetic sequences in drum sizes and geometric shapes such as cylinders and truncated cones. This research employs a literature study method to collect and analyze data from various relevant references. The results reveal that Gordang Sambilan offers contextual learning opportunities through geometric analysis, such as circumference, surface area, and volume of cylinders. Integrating Gordang Sambilan into mathematics learning not only helps students grasp mathematical concepts more concretely but also strengthens their appreciation of local culture. Hence, leveraging ethnomathematics from Gordang Sambilan can serve as an innovative strategy in mathematics education while preserving cultural heritage amidst globalization.